Web design attributes guideline to reinforce user trust, satisfaction, and loyalty for Malaysian university students / Ranjen Naidu Vasudiven - Ranjen Naidu , Vasudiven (2021)
Web site design is the most crucial factor influencing the online e-commerce business. It determines the customer's trust in the products and owners, increasing sales and recognizing its brand. There is currently no reference to understanding Malaysian university students' user preference in web site design. For this study, we evaluated Malaysian university students' user preferences for website design attributes mainly comprised of (interactivity, navigation typography, colour, and content quality). The analysis of the user preferences on the website attributes, the relationship of the attributes with the Malaysian cultures, and the findings based on the three Malaysian mostly visited bookstore websites were done. The hypothesis formed based on the literature review, and analysis of the three primarily Malaysian bookstore websites for each web attributes was discussed. Based on the hypothesis, developed a prototype, an online e-commerce book store system known as Ranjen Bookstore, was designed as a guideline. Students (n=30) participated in the test by logging the time taken for each of them, starting from the login page until the end, where they have completed the purchase by adding the items to the cart. Furthermore, the collected data based on the time logged by the 30 students in the system was analyzed. All the five web site design attributes are essential to design aspects for the development of user loyalty, satisfaction, and trust for Malaysian University students; hence, an end product, an online bookstore developed focusing mainly on the user interface incorporating these five web site design attributes. This research confirmed that the user interface helped establish trust, loyalty, and satisfaction between the user and the system. Ranjen Bookstore can be used as a reference or deciding factor by the developer when planning to design the website for Malaysian University students.